2013
DOI: 10.1371/journal.pone.0074743
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Nanoencapsulated Exogenous Trypsin Biomimics Zymogen-Like Enzyme in Fish Gastrointestinal Tract

Abstract: Exogenous proteolytic enzyme supplementation is required in certain disease conditions in humans and animals and due to compelling reasons on use of more plant protein ingredients and profitability in animal feed industry. However, limitations on their utility in diet are imposed by their pH specificity, thermolabile nature, inhibition due to a variety of factors and the possibility of intestinal damage. For enhancing the efficacy and safety of exogenous trypsin, an efficient chitosan (0.04%) nanoencapsulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 60 publications
2
15
0
Order By: Relevance
“…The variation in the size of nanoparticles after loading (increase or decrease) could be related to many factors including the type of loaded molecules, type of carrier molecules, the preparation conditions, and the surface charge (zeta potential). Kumari et al [20] noted that the increased diameter of ChNPs after trypsin loading might be due to the size and the molecular weight of the enzyme during the loading process and adsorption on the ChNP surface. However, in our study, the increase in GnRH-ChNP size could be ascribed to the occurrence of aggregation between GnRH-ChNPs.…”
Section: Discussionmentioning
confidence: 99%
“…The variation in the size of nanoparticles after loading (increase or decrease) could be related to many factors including the type of loaded molecules, type of carrier molecules, the preparation conditions, and the surface charge (zeta potential). Kumari et al [20] noted that the increased diameter of ChNPs after trypsin loading might be due to the size and the molecular weight of the enzyme during the loading process and adsorption on the ChNP surface. However, in our study, the increase in GnRH-ChNP size could be ascribed to the occurrence of aggregation between GnRH-ChNPs.…”
Section: Discussionmentioning
confidence: 99%
“…Empty nanoparticles (CW) without TTI were also prepared, using a 1:1 ( w / w ) ratio of encapsulating agents. The chitosan purification step was performed based on Kumari et al [21] with modifications proposed by Queiroz et al [16].…”
Section: Methodsmentioning
confidence: 99%
“…A number of polymeric compounds and lipids are being used in the medical field to improve the delivery efficiency of enzymes, drugs and other compounds. In this regard, Kumari et al (2013) developed an efficient chitosan nanoencapsulation-based controlled delivery system for enhancing the efficacy of exogenous trypsin in fish gastrointestinal tract. The results of a 45-day feeding trial with Rohu (L. rohita) showed that nanoencapsulated trypsin mimics zymogen-like proteolytic activity via controlled release improving growth rate and nutrient digestibility.…”
Section: Enzyme Sources and Characteristicsmentioning
confidence: 99%